Scour Depth Estimation on Abutment With HEC RAS and Some Empirical Equation - Indra Agus; Munafri Alwys; Wisafri Wisafri; Dalrino Dalrino; Noftar Yolanda; Welfi yani (Jurnal Ilmiah Rekayasa Sipil, 2020)
Toe Scour around abutment will be very dangerous and cause loss of stability on the bridge. The case of structure failure on Batang Kalu bridge in Korong Pasa Usang Nagari Kayu Tanam, Padang Pariaman Regency on Monday (10 December 2018) is a clear example of toe scouring. A case study of toe scour was on the Batang Kalu River bridge structure has been carried out. Rainfall data closest to the study location, Kandang Empat Station was used to minimize the errors in the calculation of flood discharge design. Numerical modeling with HEC RAS and scouring estimation with some empiric equation was conducted to predicting scour depth on abutment. Simulation results show scour depth results to an average of 2.731 m and close to the scour depth that occurred in the field (2.83 m). Results showed that the local scouring in the Batang Kalu River bridge structure can be suspected as the influence of the increasing river steepness. Discharge that is triggered by heavy rain with a long duration and increased river flow velocity due to steepness has the potential to create a very intense scouring. Increasing of steepness may have been caused by sand mining activities in the upper reaches. Further studies are needed to see the potential slope changes due to exploitation in the Batang Kalu River upper reaches